Automatic Generation Method of Different Stand Collar Patterns (Journal of Fiber Bioengineering and Informatics, 2024)
As technology continues to advance, there is a growing interest in personalized customization withdiverse styles and a high degree of fit. To address challenges such as long production cycles and highlabor and material costs associated with personalized customization, there has been significant researchon automatic pattern generation. However, most of these studies focus on relatively single garmentstyles. Therefore, this paper proposes a method for automatically generating multi-style collar patterns.First, by analyzing the characteristics of stand collar styles, the modules of stand collar are determined,and the control attributes and methods of each module are determined according to the actual needs.Based on this, a modular design method for stand collar is constructed; the neck parameters andstand collar structure are statistically analyzed, and a mapping model between neck parameters andstand collar structure is established; then, the relationship between stand collar modules and paperpatterns is analyzed, and a relationship model between numerical control modules and paper patternparameters is established to achieve the purpose of driving stand collar structure parameters by standcollar styles; then, according to the stand collar structure design method, the key points of the patternare parameterized, thus realizing the parametric design of the stand collar pattern; finally, using Matlabsoftware, different components are coordinated, and the modular design method and parametric designof stand collar are comprehensively applied to realize the automatic generation of different styles of standcollar patterns. The research shows that the automatic pattern generation method established in thispaper can meet the automatic pattern generation of different stand collar styles, and reduce some humanand material costs for the pattern making process in the clothing industry.